The Effect of First Case Covid-19 Announcement on Average Trading Volume Activity of Pharmaceutical Sector Companies - Hiqmatus Sholichah; Suwinto Johan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
Indonesia announced its first case of Covid-19 on March 2, 2020. This research aims to find significant differences in the trading volume activity of pharmaceutical companies before and after the Covid-19 first case announcement. The data have been obtained 3, 10, and 14 days before the announcement and on the 3rd, 10th, and 14th days after Indonesia first announced the covid-19 coronavirus. The data has been processed using SPSS 26 version through a One-sample Kolmogorov Smirnov t-test. The results show that there is a significant difference in the transaction volume of the pharmaceutical stock company before and after Indonesia’s first announcement of the covid-19 case. This is indicated by a significance value of 0.00 <0.05, which means that the transaction volume after the announcement shows an increased value compared to the volume before the announcement. Indonesia mengumumkan kasus pertama Covid-19 pada 2 Maret 2020. Penelitian ini bertujuan untuk mengetahui perbedaan signifikan volume transaksi perusahaan farmasi sebelum dan sesudah pengumuman kasus pertama Covid-19. Pengambilan data dilakukan 3, 10, dan 14 hari sebelum pengumuman dan pada hari ke-3, ke-10, dan ke-14 setelah Indonesia pertama kali mengumumkan virus Covid-19. Data diolah menggunakan SPSS versi 26 melalui uji t satu sampel. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan pada volume transaksi perusahaan saham farmasi tersebut sebelum dan sesudah pengumuman kasus Covid-19 pertama di Indonesia. Hal ini ditunjukkan dengan nilai signifikansi 0,00 < 0,05 yang berarti volume transaksi setelah pengumuman menunjukkan nilai yang meningkat daripada volume sebelum pengumuman.